Parque comercial El Malecón, Flandes, Tolima (2021)
The present research work aims to encourage tourism through a design in the environmental axis in the Magdalena river round, through direct observation and information provided by research, EOT and web pages, it was possible to identify and know that the municipality of Flandes (Tolima) does not have a public scenario that guides and develops commercial growth strategies, as a result of this in the municipality the economic income has decreased and the scarce treatment of the potentialities of the heritage, affecting the population Due to the fact that there is no policy or brand of the municipality for its external sale, so there is little flow of tourists.